2011
DOI: 10.1186/cc10368
|View full text |Cite
|
Sign up to set email alerts
|

Assessing left ventricular systolic function in shock: evaluation of echocardiographic parameters in intensive care

Abstract: IntroductionAssessing left ventricular (LV) systolic function in a rapid and reliable way can be challenging in the critically ill patient. The purpose of this study was to evaluate the feasibility and reliability of, as well as the association between, commonly used LV systolic parameters, by using serial transthoracic echocardiography (TTE).MethodsFifty patients with shock and mechanical ventilation were included. TTE examinations were performed daily for a total of 7 days. Methods used to assess LV systolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 55 publications
8
58
0
1
Order By: Relevance
“…4,5 Our intra-observer variability for CO TTE measurement was low (much lower than the changes in CO we observed during PLR and after fluid loading) and similar to previous reports. 20 Moreover, we required high-quality TTE criteria, which explains the high rate of exclusion and strengthens the internal validity of our results. It is noteworthy that TTE offered a continuous beatto-beat and noninvasive CO measurement while esCCO averaged 64 consecutive heart beats.…”
Section: Discussionsupporting
confidence: 62%
“…4,5 Our intra-observer variability for CO TTE measurement was low (much lower than the changes in CO we observed during PLR and after fluid loading) and similar to previous reports. 20 Moreover, we required high-quality TTE criteria, which explains the high rate of exclusion and strengthens the internal validity of our results. It is noteworthy that TTE offered a continuous beatto-beat and noninvasive CO measurement while esCCO averaged 64 consecutive heart beats.…”
Section: Discussionsupporting
confidence: 62%
“…Echocardiographic studies have reported similar results with a reduced global systolic function in 30 to 60% of septic shock patients (23,35) and reversibility in survivors (26,28,102). The definition of systolic dysfunction has varied (LVEF 45 to 55%) and comparison between studies is therefore complicated.…”
Section: Echocardiographysupporting
confidence: 57%
“…Varying use of vasopressor and inotropic drugs, rapid fluid shifts and positive pressure ventilation are just some of the challenges during image acquisition and interpretation. However, the addition of observer dependency to the interpretation of the echocardiographic findings has been remarkably less studied in intensive care than in cardiology (35). Thus, the extent to which the differing results in the incidence and spectrum of cardiac dysfunction in sepsis is related to the reading of the echocardiograms is unclear.…”
Section: Variability Of Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a cohort of 50 patients undergoing mechanical ventilation with shock, LVEF evaluation with the Simpson technique displayed the worst intra and inter-observer variability [30]. STE is an operator-independent technique with low inter-observer variability (from 2 [31] to 13% [32]) regarding strain data but higher variability regarding strain rate [28]. In patients with mechanical ventilation, we found an inter-observer variability of 8% [25] while others [20,24] have also found a good inter-observer agreement with a Bland-Altman analysis.…”
Section: What Could Ste Add In the Icu Field?mentioning
confidence: 99%